Characteristics of adult dreams in the perspective of the concept of passivity in the meaning of transactional analysis - Marika Oracz (Edukacyjna Analiza Transakcyjna)
Charakterystyka marzeń osób dorosłych w perspektywie koncepcji pasywności w rozumieniu analizy transakcyjnej